Lytic bacteriophage disrupts biofilm and inhibits growth of pan-drug-resistant Listeria monocytogenes in dairy products - Abdullah, Elsayed M.; Elariny, Eman Y. T.; Abdelaziz, Rewan; Albalawi, Abeer S.; Almutrafy, Abeer M.; Zaki, Mohamed Samir A.; Abdel-Karim, Safaa A.; Tartor, Yasmine H. (Frontiers in Microbiology, 2025)
Listeria monocytogenes is a major foodborne pathogen whose presence presents a continuous challenge in the food industry. A key issue is the formation of biofilms, which are complex microbial communities that cling to surfaces. These biofilms are incredibly resilient, making them tough to eliminate and manage. Therefore, it is crucial to find new and innovative ways to prevent and remove them. This study investigated the prevalence of L. monocytogenes in raw milk and Kareish cheese samples, as well as its resistance to antimicrobials and its ability to form biofilms. We also isolated and characterized a lytic bacteriophage to explore its anti-biofilm potential. Listeria species prevalence was 20% (n = 24/120 samples), higher in raw milk (31.7%) than Kareish cheese (8.3%). Eighteen isolates (15%) were identified as L. monocytogenes. High resistance rates were observed, notably to cefotaxime and cotrimoxazole. One pan-drug resistant (PDR) isolate was found in Kareish cheese, and the other 17 isolates were multidrug resistant (MDR). All L. monocytogenes isolates formed biofilms, categorized as weak: n = 7, moderate: n = 9, and strong: n = 2. We isolated a lytic bacteriophage, vB_LmoP_M15, which demonstrated lytic activity against all L. monocytogenes isolates, including both MDR and PDR strains. This phage belongs to the Podoviridae family, characterized by a short, non-contractile tail and an icosahedral head. Its genome size was estimated to be approximately 48.5 kb based on agarose gel electrophoresis of undigested phage DNA using a high molecular weight marker, and its restriction pattern was analyzed using HinfI, HindIII, and HaeIII enzymes. It has a latent period of 15 min and a burst size of 172 phage particles per infected cell. Phage vB_LmoP_M15 demonstrated significant antibiofilm activity (p < 0.05 to p < 0.0001). It effectively disrupted preformed biofilms and inhibited biofilm formation by MDR/PDR isolates. Application of vB_LmoP_M15 in pasteurized milk resulted in a significant reduction of L. monocytogenes counts by 2.45 log10 CFU/ml over 7 days at 30°C. These findings underscore the significant potential of phage vB_LmoP_M15 for controlling L. monocytogenes contamination and biofilms in dairy products.